Comparative Analysis of Encrypted Keyword Search in Cloud Data - Dr Mukesh Singla (International Journal of Advanced Science and Technology, 2020)
The growing demand of decentralised computing in the world has forced us to find ways of smartly managing the data, which is very secure, and accessible. In doing so we have made the data storage highly secure by storing of the data securely using the encrypted forms of its far as security is concerned. However, when we talk about accessibility it also deals in random with the searching of the data in encrypted form in which the search keyword is also encrypted to have a multitude of security where even the keyword is secure. Many methods for Encrypted search have been introduced. In this paper, we are analysing and comparing three of those major methods.